THE CORRELATION ANALYSIS BETWEEN EMPLOYER BRANDING AND EMPLOYEE SATISFACTION AND LOYALTY: CASE STUDY AT ONE OIL COMPANY IN INDONESIA - Ria Renny Christiana; Donny Oktavian Syah (Jurnal Ilmiah Ekonomi Bisnis, 2017)
This study focuses on analyzing and understanding correlation between Employer Branding and Employee Satisfaction and loyalty at PT. XYZ, a global oil and gas company which operate in 90 countries. The company listed on number 14 out of 50 companies as preferred employer in 2010 for enginering background students based on Universum study on  2011.  The challenge that company  face is the declining  rank compare to previous year. The result of this quantitative research is based on random sampling survey of 44 respondents of PT.XYZ employees (one oil company which operated in Indonesia). The research reveals that there are still perception gap between employee and company expectation. Whilts  To measure degree of relationship of  employer branding and satisfaction and loyalty,chi square analysis is being used.The result of chi square score indicate that there significant relationship between employee branding with employee satisfaction. However, there is no relationship between employee branding with loyalty. Keywords: Brand, Employer branding, Employee loyalty, Employee satisfaction.